Characterization and biological activity of Taishan Pinus massoniana pollen polysaccharide in vitro. - Shifa Yang; Kai Wei; Fengjuan Jia; Xue Zhao; Guolin Cui; Fanxia Guo; Ruiliang Zhu (PLoS ONE, 2015)
Taishan Pinus massoniana pollen polysaccharide (TPPPS) improves cellular and humoral immune responses of animals and is a novel potential immunomodulator. However, the components of TPPPS have not been recognized. To investigate the composition of TPPPS, crude polysaccharide was obtained from Taishan P. massoniana pollen through water extraction and ethanol precipitation. Three homogeneous polysaccharide fractions (TPPPS1, TPPPS2, and TPPPS3) were purified from TPPPS by DEAE-cellulose column chromatography. The average molecular weights of the three polysaccharides were 56, 25, and 128 kDa, respectively. Results of high-performance liquid chromatography (HPLC) showed that TPPPS comprised mannose, ribose, xylose, glucuronic acid, galacturonic acid, glucose, galactose, and arabinose. The biological activity assays showed that TPPPS2 and TPPPS3 significantly promoted spleen lymphocyte proliferation, and that TPPPS3 showed better effect than TPPPS2. TPPPS3 enhanced the secretion of cytokine IL-2 and TNF, whereas TPPPS2 mainly elevated IL-2 secretion. By contrast, TPPPS1 exhibited other effects, and it induced the highest amount of NO production, thereby indicating that TPPPS1 had the best antioxidant activity. TPPPS3 at 50 μg/mL significantly inhibited the proliferation of subgroup B Avian Leukosis virus (ALV-B) through virus adsorption interference in vitro. Results indicated that TPPPS comprised three main components, among which, TPPPS1 mainly showed antioxidant effects, whereas TPPPS2 and TPPPS3 played key roles in immunomodulation, especially TPPPS3. Further studies on the use of a reasonable proportion of TPPPS1-3 may facilitate the development of an effective immunomodulator.